17 Imaging of LVAD complications: experience from mayo clinic. (9th April 2018) - Kam, Kevin KH
Abstract : Left ventricular assist devices (LVADs) are mechanical support devices for patients with end-stage heart failure. Echocardiography plays a pivotal role in different aspects including patient selection, perioperative imaging guidance, management of complication, optimisation of LVAD efficacy and assessment of ventricular recovery. 1 Post-surgical transthoracic echocardiography (TTE) evaluation should be performed for assessing overall structure and haemodynamics of left and right heart, valvular regurgitation, inflow and outflow cannula evaluation and intracardiac thrombus detection. Small LV dimensions post LVAD support, as demonstrated by marked deviation of interventricular septum towards the left side may signify excessive high pump speed. Right ventricular function evaluation after LVAD implantation is crucial as it may paradoxically worsen due to excessive LV unloading. New-onset aortic regurgitation (AR) occurs in approximately 25%–30% of patients one year after LVAD implantation. 2 It not only causes adverse effects on LVAD performance but also increases future morbidity and mortality. 3 Assessment of AR is technically challenging in LVAD patients. Regurgitant fraction is superior to traditional TTE parameters (e.g. vena contracta) in assessing LV filling pressures. 4 As for cannula evaluation, high Doppler velocity >1.5 m/s at inflow may result from malposition or inflow obstruction, whereas low velocity may indicate inflow cannula thrombosis. Outflow graft abnormality should be suspected when the Doppler velocity >2 m/s. Although adequate anticoagulation is indicated post LVAD implantation, there is still risk of intracardiac thrombosis. The typical sites of thrombus formation include the atria, LV apex and aortic root. References: . Stainback RF, Estep JD, Agler DA, et al. Echocardiography in the management of patients with left ventricular assist devices: Recommendations from the American society of echocardiography. J Am Soc Echocardiogr2015;28:853–909. . Cowger J, Pagani FD, Haft JW, et al. The development of aortic insufficiency in left ventricular assist device supported patients. Circ Heart Fail2010;3:668–74. . Toda K, Fujita T, Domae K, et al. Late aortic insufficiency related to poor prognosis during left ventricular assist device support. Ann Thorac Surg2011;92:929–34. . Grinstein J, Kruse E, Sayer G, et al. Accurate quantification methods for aortic insufficiency severity in patients with LVAD. JACC: Cardiovascular Imaging2016;9:641–51.